Opini Publik di Media Sosial tentang Tokoh Masyarakat yang Bertransformasi Menjadi Anggota DPR RI - Rizka Rahmawati; Nasyaya, Annada (Wardah, 2025)
The government has an important role towards the public as a leader, one of which is the People's Representative Council of the Republic of Indonesia. Institutions that make laws and represent the voice of the people. This research aims to find out public opinion on social media related to the transformation of public figures into DPR RI. Seeing that there are several public figures who contribute to the public by occupying positions in the DPR RI and accompanied by the phenomenon of a number of political parties involving public figures. This study looks at public opinion regarding the Indonesian DPRI who has a background as a public figure in the 2019 - 2024 period. The research method used is descriptive quantitative with content analysis to look at the content of public tweets on Twitter or X media. Crawling the data using Google Collaboratory, 3009 tweets were found using keywords determined by the time filter 1 October 2019 – 28 November 2023. The data was categorized (coding) and analyzed using Kriyantono's theory of several categories of public opinion. This research found that there were dominant categories such as positive opinion with a percentage of 57% or 1,727 tweets. Another finding is that there are indicators that are the most dominant, such as indicators of approval conveyed by the public after going through categorization.